Modern African banking cases - Milner, Alan.; Abrahams, Susan (Oxford : African Law Reports, 1973)
The book is intended to meet the need of lawyers and teachers for up -to-date information about African developments.
Includes index.
II 15/01/2019
Loans
Keywords: Banking law